(untitled) (Papeles, 2013)
This paper develops the concept of soft power perspective initiated by Joseph Nye, in opposing sense of the hard power, it is defined from the coercion of military power and political economy, in contrast to the power of institution-building linked with the first one, it builds values and traditions with communicating vessels with the inclusion of minorities, solidarity and social equity. The implementation of soft power mean in a broader sense incorporating modernity consensual discussion on the validity of the paths of civilization and not just the passage under the paths of market forces, even in the worst case of military forces. However, we could not ignored the crucial role of the market in terms of coordinating and optimizing of the resources allocation (although sometimes by perverse way), and military forces as guarantor of order and property, essential elements of a modern life.